Tingkat Kepuasan Siswa Terhadap Kualitas Layanan Pembelajaran Geografi Secara Daring Pada Masa Pendemi Covid-19 - A. Rohimah; Andrias Andrias; La Ode Nursalam; Surdin Surdin (Jurnal Penelitian Pendidikan Geografi, 2025)
The implementation of changes in the system for organizing activities from offline to online made Senior High School 2 Kendari to carry out online learning. This change encourages education service providers to pay more attention to student satisfaction. This study aims to determine the quality and level of student satisfaction with online Geography learning services during the Covid-19 pandemic. The research method used in this study is survey research with a quantitative approach. Data collection techniques in this study used questionnaires and documentation. Data analysis techniques in this study used descriptive statistics. The results showed that the five indicators were considered to have met students' expectations, with a recapitulation result of 57% on the Good indicator. In the variable level of satisfaction with the quality of online Geography learning services, it is known that the five indicators have also met student expectations, with a recapitulation result of 64% in the Satisfied category. So that it can be interpreted that the level of student satisfaction with the quality of online Geography learning services in class XII IPS Senior High School 2 Kendari is in the satisfying category.